A hybrid approach to determine patients critical situation using expression & posture with convolutional neural network & Blazepose algorithm - Islam, Abrar; Acanto, Orbin Ahmed; Drishty, Mehzabin Islam; Zaman, Samonty; Ahmed, Jaber (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.